Implications for household health expenditure in China’s ageing population: based on Red Herring hypothesis - Xuyang Du; Hualin Wei; Xianbo Zhang (BMC Public Health)
Abstract The rising healthcare costs due to population aging present a complex issue, with debate centering on whether these costs are driven by aging or end-of-life care. This study examines healthcare expenditures in Chinese households using data from the 2005 and 2018 Chinese Longitudinal Healthy Longevity Survey. By applying the Heckman select model and a two-part model, the research innovatively includes time to death, income, social security and health level in the benchmark regression in order to validate the recent some new Red Herring hypothesis. The findings show that time to death is the primary determinant of healthcare expenditures, while the effect of aging is minimal. Income, social security, and health status also significantly influence health expenditure, but they do not function as Red Herring variables.